Academic skills in the screenish era - Peter Bradley (Journal of the European Honors Council, 2020)
Our culture has begun to react to the implications of digital technology for our shared memory and individual privacy in the form of legislation like GDPR.  But the culture of higher education---specifically the dominant model of knowledge generation and transmission---stays firmly rooted in the 'bookish' tradition. Honors education was started in response to the changing world in the wake of WWII. Its core principles of engaged learning and individualization of the student experience can lead higher education to embrace the new culture of digital technology-assisted knowledge generation and transmission.